2021
DOI: 10.1016/j.atherosclerosis.2021.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol at ages 6, 12 and 24 months: Tracking and associations with diet and maternal cholesterol in the Infant Cholesterol Study

Abstract: Background and aims: There are indications for tracking of circulating total cholesterol concentration (TC) from childhood to later in life. An increased lifelong TC exposure increases the risk of developing atherosclerosis, however little is known about the determinants of TC early in life. We aimed to describe TC in Norwegian offspring aged 6, 12 and 24 months, and to explore if maternal TC, breastfeeding and offspring diet are associated with offspring TC. Methods: In this cross-sectional study, mothers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Taageby Nielsen’s data demonstrate tracking of levels of LDL-C, non-HDL-C, and Lp(a) from birth to 2 months and to 14–16 months of age, consistent with previous data showing tracking of total cholesterol from 6 to 12 month of age. 2 The Young Finns Study (YFS), 7 showed a strong correlation between total cholesterol and LDL-C concentration at 3 years of age and in adulthood after 27 years of follow-up, demonstrating that the cholesterol levels at young age track into adulthood 7 and supporting the conclusion of the authors that ‘Concentrations at birth may thus be used as an indicator of high concentrations later in life’. 1…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Taageby Nielsen’s data demonstrate tracking of levels of LDL-C, non-HDL-C, and Lp(a) from birth to 2 months and to 14–16 months of age, consistent with previous data showing tracking of total cholesterol from 6 to 12 month of age. 2 The Young Finns Study (YFS), 7 showed a strong correlation between total cholesterol and LDL-C concentration at 3 years of age and in adulthood after 27 years of follow-up, demonstrating that the cholesterol levels at young age track into adulthood 7 and supporting the conclusion of the authors that ‘Concentrations at birth may thus be used as an indicator of high concentrations later in life’. 1…”
mentioning
confidence: 61%
“…However, at 14–16 months of age, the levels are similar. We have previously shown that in infants at 6 months of age, plasma levels of total cholesterol were similar to adult levels, 2 potentially suggesting that infants reach their adult levels between 2 and 6 months of age.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…However, breastfeeding increased concentrations of triglycerides and remnant cholesterol significantly and thereby diet has a larger impact than genetic contributions on these parameters. Previous studies have suggested that lipid concentrations in early childhood (2–12 months of age) are correlated with concentrations in later childhood (1–5 years of age) 37 , 38 and that childhood and adolescent concentrations (13–18 years of age) correlate with adult concentrations (27-year follow-up). 39 However, it is still unclear if early childhood concentrations track all the way to adulthood, emphasizing that further studies are needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…We know from the Cardiovascular Risk in Young Finns study that lipid levels track through life, meaning that children with high LDL-C levels are more likely to become adults with high LDL-C levels. 4 We also know that there is a correlation between maternal and offspring lipid levels, [5][6][7] meaning that children with high LDL-C levels are more likely to have parents with high LDL-C levels. Therefore, we believe that within any population, children with LDL-C levels in the uppermost quintiles should be offered genetic testing for FH-causing variants and cascade screening of relatives, as well as a family-based approach to lifestyle management and drug therapy.Detecting and treating hypercholesterolemia from early in life may have profound implications for the lifetime risk of atherosclerotic cardiovascular disease (ASCVD).…”
mentioning
confidence: 99%